A Literature Review on the Study of Income Distribution, Education and Education Return Rate - Based on Family Background and Gender Differences - Han, Qiong (Journal of Accounting, Business and Finance Research, 2019)
The study of income distribution, education input and education return rate has always been a hot topic in the theoretical circle. Most of the existing researches have drawn a conclusion that there is a significant positive correlation between the years of education and the income level. There is a two-way causal relationship between income distribution and education. In addition, the distribution of education and the rate of return on education will also have an impact on education. This paper aims to focus on the impact of gender differences in income distribution on education based on previous research, while focusing on the distribution of education and the rate of return on education in different genders. Based on the specific quantitative indicators of the differences, some theoretical support and policy recommendations on education and education reform are given.